An interesting fact

#1

Just found out it accidentally

X percent of Y equal Y percent of X

check it, math is so beautiful

#2

Nice!

#3

math is so beautiful

Indeed!

Here's a mathematical proof for those interested, but why not try it yourself first!

If Z = X percent of Y
Z = (X/100)Y
Z = Y(X/100)
Z = (YX)/100
Z = X(Y/100)
Z = (Y/100)X
Z = Y percent of X

therefore
X percent of Y = Y percent of X

#4

That’s interesting!

#5

Hm. Interesting

#6

#7

Where’d you find this project

#8

A little birdie found it

#9

That makes no sense but uhh

#10

A little birdie named search bar

#11

I mean what account or project

#12

I don’t remember

#13

Smh ok

#14

Yes, there is a mistake

The right side of 4th line on should be
= Y(X-Y)
= Y
= Y
= 1

but ultimately it still seems to show that 2=1

Then there’s the algebraic error that’s the point of the intended “proof”:

(X-Y) can’t be “cancelled out”
Since X=Y, (X-Y)=0
and as a rule, you can’t divide by 0
which is what was done to “cancel out” the (X-Y)

#15

You could possibly substitute the Y with X also, making X=X and divide by X on each side to get 1=1

There’s a lot of ways to solve that

#16

#17

I was going to tag you for that because I’ve seen the problem and knew it was in that step, but couldn’t find an explanation for that

#18

I’m wondering whether anybody had a chance to solve these problems:
21 Hardest Math Problems

#19

Lol I couldn’t if I tried.

#21

Interesting. I only looked at the first 2, but just FYI for anyone trying them: The explanation of #2 is wrong. It should say:

#2: First let us set up the equation we are told—that the product of c and 3 is b.

3c=b

Now we must isolate c so that we can add its value to 3.

3c=b

c=b/3

Finally, let us add this value to 3.

b/3+3

Our final answer is E, b/3+3